Zrównoważona karta wyników w państwowej szkole wyższej - Ossowski, Marek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The aim of the article is to present a model of the balanced scorecard for public high school. In the introduction of the paper the author identifies four perspectives for public high school which are: student, internal process, research and development, and financial perspectives. In the further part the specification of measures describing every perspective is mentioned. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 292-306